External Field‐Driven Untethered Microrobots for Targeted Cargo Delivery. Issue 5 (4th December 2021) - Zhu, Shilu; Chen, Yin; Liu, Guangli; Qian, Haisheng; Niu, Fuzhou; Wang, Ying; Zhao, Yuliang; Luo, Tingting; Yang, Runhuai
Abstract: Untethered microrobots (UMRs) propelled by multiple external power sources have emerged as promising tools for biomedical applications, such as targeted cargo delivery (TCD), microsurgery, thrombolysis, medical imaging, etc. In particular, owing to their minimal invasiveness and capability of accessing hard‐to‐reach regions of the human body in a controllable manner, the application of UMRs for TCD is of great interest in recent years. Here, the state‐of‐the‐art UMRs in this regard are presented, focused on targeted drug and cell delivery systems. Meanwhile, this review systematically details recent research studies on the use of UMRs in TCD, containing their constituent materials (functional, scaffold, and smart materials), fabrication methods, and three types of external propulsion energy sources concerning their mechanisms and corresponding typical designs. Subsequently, various strategies for controlled drug release are summarized, as well as the latest targeted cell delivery systems and relevant cell manipulation in vitro or in ex vivo. Finally, the current challenges to clinical translation faced by the UMRs and future perspectives on this field are highlighted. Abstract : Untethered microrobots (UMRs) hold great promise in biomedical applications and are expected to make innovative progress in this field. This review systematically introduces UMRs from four aspects, including their material components, fabrication methods, three common external physical fields as power sources and their applications in targeted cargo (drug and cell) delivery, and gives an outlook on future research.